Preventing prejudice by preserving the spirit of mental health legislation during the COVID-19 national emergency. (October 2020) - Ouliaris, Calina; Sheahan, Linda; George, Duncan
Objective: The COVID-19 national emergency activates legislative powers that allow a proportional infringement upon individual liberties. We canvas the complex legal landscape governing mental health consumers in this climate, highlight ethical considerations in application of the law and offer a simple algorithm to navigate this space. Conclusion: In times of emergency, it is crucial that we uphold the safeguards embodied within mental health legislation to prevent prejudicial treatment of mental health consumers.